Terebélidos (Terebellidae: Polychaeta: Annelida) del Caribe colombiano - Mario H. Londoño-Mesa (Biota Colombiana, 2011)
Polychaetes have a high diversity and abundance in all oceans. They have important role as biological indicators of marine water quality. In Colombia, they have been studied for about 30 years, in which 43 families, 138 genera and 253 species have been identified, from central and north Colombian Caribbean coasts. The aim of this research was the taxonomic analysis of material belonging to the family Terebellidae, deposited in the Invemar Invertebrate Collection. Eight genera and 11 species of terebellids were previously identified; nevertheless, after this research, these numbers were increased to ten genera, and 17 species. The scarce information about polychaetes available in Colombia, and the lack of stardardized, updated taxonomic world revisions, not only for terebellids but also for the entire group of polychaetes, led to many incorrect species identifications, and the belief that some species are cosmopolitan in distribution. Anincrease in funding of basic taxonomic research will permit better estimates of the true polychaete diversity found in Colombian seas.